Exposure to Adverse Childhood Experiences (ACEs) and Stress among the Community-based Urban Pediatric Population in Korea - Lee, Mi-Sun; Kim, Hyun-Soo; Bhang, Soo-Young (Journal of Korean medical science, 2020)
This study aimed to investigate the impact of exposure to adverse childhood experiences (ACEs) and stress among the community-based urban pediatric population in Korea. In 2017, the analysis was conducted on 3,937 children and adolescents in an urban area in Korea based on the impact of actual traumatic experience, addiction, and mental health. The respondents were excluded if they were missing data on the survey, resulting in a final sample size of 3,556. The collected data were analyzed by applying cross-sectional and correlation analyses. Among the respondents in the study group (mean age = 13.77), 43.1% were boys (n = 1,532) and 56.9% were girls (n = 2,024). Overall, 23.5% (n = 835) reported at least one ACE and 1.8% (n = 63) reported experiencing four or more ACEs. Emotional abuse (13.2%) was the most commonly reported ACE, followed by abandonment (7.7%) and physical abuse (7.5%). Self-reported measures of stress were associated with the ACE scores. This is the first study of self-reported ACEs from a community-based pediatric population in Korea. We found that the number of the students revealed more than one ACEs was similar to the data in the US community study with self-reporting among the community samples and exposure to adverse experiences is highly correlated with various stress responses.